2013
DOI: 10.1186/1477-7819-11-219
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of serum exosomal microRNAs and clinicopathologic features of patients with pancreatic adenocarcinoma

Abstract: BackgroundAltered expression of serum microRNAs (miRNAs) have been reported to correlate with carcinogenesis and progression of pancreatic adenocarcinoma (PC), but descriptions of serum exosomal miRNAs in PC are still lacking. This study was designed to evaluate serum exosomal miRNA levels in PC patients and to investigate their relationships with clinicopathologic features and prognosis.MethodsFour miRNAs (miR-17-5p, miR-21, miR-155 and miR-196a) related to PC were selected for examination in our research. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
159
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(160 citation statements)
references
References 26 publications
(31 reference statements)
1
159
0
Order By: Relevance
“…Ogata-Kawata et al (53) found that the amount of seven serum exosomal miRNAs (i.e., let-7a, miR-1229, miR-1246, miR-150, miR-21, miR-223 and miR-23a) from the serum of TNM stage I colorectal cancer patients were significantly higher than in healthy controls; this finding suggested that serum exosomal miRNAs may serve as significant biomarkers for the early detection of primary colorectal cancer (53). One study of pancreatic adenocarcinoma (PC) found that serum exosomal miR-17-5p and miR-21 were significantly elevated in the advanced stage and metastatic PC patients; moreover, the diagnostic sensitivity and specificity were 72.7 and 92.6% for miR-17-5p and 95.5 and 81.5% for miR-21, respectively (54). In the present study, microarray analysis of plasma from esophageal cancer patients and healthy controls identified 20 miRNAs that could distinguish the plasma from ESCC patients and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Ogata-Kawata et al (53) found that the amount of seven serum exosomal miRNAs (i.e., let-7a, miR-1229, miR-1246, miR-150, miR-21, miR-223 and miR-23a) from the serum of TNM stage I colorectal cancer patients were significantly higher than in healthy controls; this finding suggested that serum exosomal miRNAs may serve as significant biomarkers for the early detection of primary colorectal cancer (53). One study of pancreatic adenocarcinoma (PC) found that serum exosomal miR-17-5p and miR-21 were significantly elevated in the advanced stage and metastatic PC patients; moreover, the diagnostic sensitivity and specificity were 72.7 and 92.6% for miR-17-5p and 95.5 and 81.5% for miR-21, respectively (54). In the present study, microarray analysis of plasma from esophageal cancer patients and healthy controls identified 20 miRNAs that could distinguish the plasma from ESCC patients and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, miRNAs can be readily detected in small-volume samples using specific and sensitive quantitative real-time PCR (qRT-PCR) (68). Additionally, EV-associated miRNAs have been used as diagnostic and prognostic markers (20,(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79). Microarray analyses of miRNAs in EV-enriched fractions of serum from 88 patients with primary colorectal cancer (CRC) and 11 healthy controls revealed that that the levels of 7 miRNAs were significantly higher in the serum EVs of CRC patients compared with serum EVs from healthy donors (74).…”
Section: The Emerging Role Of Evs In Cancer Immunologymentioning
confidence: 99%
“…Serum exosomal miR-17-5p and miR-21 were highly expressed in pancreatic adenocarcinoma patients (46). Ren et al (47) analyzed gastric cancer-derived exosomes by next-generation sequencing technology, and demonstrated that these exosomes contained more proteins and RNAs than normal gastric mucosal epithelial cell-derived exosomes, with miRNA-21-5p and miRNA-30a-5p having the most abundant miRNA profiles.…”
Section: Early Detection By Exosomal Mirnasmentioning
confidence: 99%